CORPORATE GOVERNENCE, PROFITABILITAS DAN NILAI PERUSAHAAN - Adyawan Putra Raharja; Nova Novita (Ibs Press, 2026)
This paper examines the effects of corporate governance indicators—namely audit committee size, managerial ownership, and institutional ownership—as well as profitability on firm value. Firm value is measured using Tobin’s Q, audit committee size is measured by the number of audit committee members, managerial ownership is measured by the percentage of shares held by top management, institutional ownership is measured by the percentage of shares held by institutional shareholders, and profitability is measured using return on equity (ROE). Based on a sample of transportation companies, the results indicate that audit committee size has a negative effect on firm value, managerial ownership has no effect on firm value, institutional ownership has a negative effect on firm value, and profitability has no effect on firm value. These findings suggest that the presence of an audit committee and a high level of institutional ownership do not necessarily enhance the value of transportation companies and may even be perceived negatively by the market when they are not accompanied by effective oversight, independence, and transparency. Therefore, companies should prioritize the quality of governance over mere formal compliance with governance structures, while investors should consider the effectiveness of oversight mechanisms and companies’ fundamental prospects more comprehensively when assessing firm value.